Diversity of Ligninolytic Enzymes and Their Genes in Strains of the Genus Ganoderma: Applicable for Biodegradation of Xenobiotic Compounds? - Torres-Farradá, Giselle; Manzano León, Ana M.; Rineau, François; Ledo Alonso, Lucía L.; Sánchez-López, María I.; Thijs, Sofie; Colpaert, Jan; Ramos-Leal, Miguel; Guerra, Gilda; Vangronsveld, Jaco (Frontiers in Microbiology, 2017)
White-rot fungi (WRF) and their ligninolytic enzymes (laccases and peroxidases) are considered promising biotechnological tools to remove lignin related Persistent Organic Pollutants (POPs) from industrial wastewaters and contaminated ecosystems. A high diversity of the genus Ganoderma has been reported in Cuba; in spite of this, the diversity of ligninolytic enzymes and their genes remained unexplored. In this study, thirteen native WRF strains were isolated from decayed wood in urban ecosystems in Havana (Cuba). All strains were identified as Ganoderma sp. using a multiplex PCR-method based on ITS sequences. All Ganoderma sp. strains produced laccase enzymes at higher levels than non-specific peroxidases. Native-PAGE of extracellular enzymatic extracts revealed a high diversity of laccase isozymes patterns between the strains, suggesting the presence of different amino acid sequences in the laccase enzymes produced by these Ganoderma strains. We determined the diversity of genes encoding laccases and peroxidases using a PCR and cloning approach with basidiomycete-specific primers. Between two and five laccase genes were detected in each strain. In contrast, only one gene encoding manganese peroxidase or versatile peroxidase was detected in each strain. The translated laccases and peroxidases aminoacid sequences have not been described before. Extracellular crude enzymatic extracts produced by the Ganoderma UH strains, were able to degrade model chromophoric compounds such as anthraquinone and azo dyes. These findings hold promises for the development of a practical application for the treatment of textile industry wastewaters and also for bioremediation of polluted ecosystems by well-adapted native WRF strains.